Karakteristik Fisik Dan Kimia Limbah Padat Dari Industri Karet Remah Dengan Masa Inkubasi Berbeda - Muhammad Helmy Abdillah (Program Studi Budidaya Tanaman Perkebunan, Politeknik Hasnur, 2020)
Demand for crumb rubber and block rubber from abroad to increase thus encouraging crumb rubber agro industry factories in Indonesia to increase of the production, but this is not matched by environmental quality that should be increasingly considered. Pollution that appears to be seen in the form of changes in the color of water and solid material from the washing of latex crumbs as sludge which leaves a damaged latex, mixed with wood and other inorganic materials. In the process of handling liquid waste in Waste Water Treatment Plant (WWTP) ponds, liquid waste can be recycled so that it can be reused to wash lumps and latex crumbs, but solid waste in the form of activated sludge at the bottom of the WWTP ponds containing damaged rubber with inorganic materials has become a polluter in the factor. In this research, the characteristics of the solid waste are analyzed to be used as soil amendment material of determining the appropriate length of incubation different, so that the waste is indeed feasible as soil amendment. This research was conducted at August 2019 to February 2020 with compare the results of the three treatment levels for the incubation period of solid waste with code T1 = 60 days after being removed from the WWTP pond; T2 = 120 days after being removed from the WWTP ponds; T3 = 180 days after being removed from the WWTP ponds, which was four repeated. Method in parametric research as temperature with mercury thermometer, color of waste compare with Munsell's soil, texture of material with skin sensing method, particle size with 1 inch sieve, moisture content with gravimatric method, and bulk density with sample ring method, as well as chemical properties of solid waste with observational variables i.e. pH (H2O) is measured with digital pH meter, Fe-total with the ortho-phenanthroline spectrophotometry method, Lead (Pb) b with the spectrophotometric HNO3 method, C-organic with the Walkley-Black spectrophotometric method, N-total with the Kjeldahl’s method, P2O5 with the Olsen’s spectrophotometric method, C-organic with the Walkley-Black’s spectrophotometric method, K2O with Morgan’s spectrophotometry method, and C / N ratio with dividing the index C of N. The best treatment is based on the approach required by SNI 19-7030-2004 and the Decree of the Minister of Agriculture No. 261 / KPTS / SR.310 / M / 4/2019. From the results of this study it was concluded that the solid waste in the T2 treatment was the best treatment that has physical properties with a temperature character of 28.6 °C, a blackish gray color with an index of 5BG 4/1, a fine textured soft lumpy, with particle size <25 mm, content water (8.7%) and bulk density (0.81 g.cm-3), as well as chemical properties with a pH of 7.02; Fe-total (0.00104 ppm); Lead (Pb) <0.01 ppm; C-organic (11.21%); N-total (1.37%); P2O5 (1.33%); K2O (0.56%) and C / N ratio of 8.18.